Research on the Relationship between Sediment Concentration and Centrifugal Pump Performance Parameters Based on CFD Mixture Model - Xinhao Wu; Peilan Su; Jianhua Wu; Yusheng Zhang; Baohe Wang (Energies, 2022)
To study the relationship between sediment concentration and the performance parameters of centrifugal pumps, Jiamakou water supply pumping station with total installed capacity of 30,880 kW was selected to analyze characteristics of the centrifugal pump in this paper. Based on a CFD mixture model, the effects of different sediment concentrations on the movement of solid–liquid two-phase flow and the performance parameters of the centrifugal pump were obtained. Then, fitting equations were established between performance parameters (head, flow rate, shaft power, and efficiency) of the centrifugal pump and sediment concentration at three working conditions (0.8 Q = 2 m3/s, Q = 2.5 m3/s, 1.2 Q = 3 m3/s) by the polynomial least-square method. Calculated values of fitting equations were compared with the measured values in centrifugal pump operation. The results show that, as the sediment concentration increases from 0.1% to 1%, the maximum volume fraction of sediment at blade outlet increased from 0.14% to 1.14%, and the maximum volume fraction of sediment at blade outlet increased from 0.7% to 2.29%. The turbulent kinetic energy inside the centrifugal pump increased from 8.74 m2/s2 to 10.78 m2/s2. The calculated values of fitting equation are in good agreement with the measured values in centrifugal pump operation, and the maximum errors of head, flow rate, and efficiency are 6.48%, 3.54%, and 2.87%, respectively. Therefore, the reliability of the fitting equations is verified. The research method can provide a reference for the calculation of performance parameters for centrifugal pumps in other water supply pumping stations with sediment-laden flow.